TI_GERICHTE 32.2019.7 vom 21. November 2018 , LAI-LAINF. Rendita limitata nel tempo confermata. Grado AI: 37% - TI Tribunale d'appello (2018)
LAI-LAINF. Rendita limitata nel tempo confermata. Grado AI: 37%